Because I said so! [compact disc, unabridged] : the truth behind the myths, tales and warnings every generation passes down to its kids - Jennings, Ken, 1974- (Tantor Audio, 2012)
Ken Jennings delivers a characteristically engaging and surprisingly useful guide, revealing the truth behind all the terrible things parents used to warn their children about.